Sesar Unjur- The Blessing of the Ocean (Short Video) - Rafee, Y.M; Awang Arshad, A.H; Abol Hassan, M.Z; Jussem, S.W (Old Kuching Smart Heritage (OKSHe), 2020)
This short video with a duration of 4 minutes and 59 seconds is a summary of the Sesar Unjur production process. The filming was done in in the Kampung Belawai, Tanjung Manis, Sarawak and funded under the Nusantara Chair grant (F03 / NRC / 1653/2018). This video has won first place in the Old Kuching Smart Heritage (OKSHe) video competition and the video can be viewed via https://www.youtube.com/watch?v=0UG-iK-0Q0I